Criticism, healing and curatorship (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this conversation, held within the framework of the Journey of the Brazilian Association of Art Critics (ABCA) of 2020, in partnership with the Federal University of Southern Bahia, the performer and psychologist Castiel Vitorino Brasileiro and professor and researcher Dodi Leal reflect on the interfaces of criticism, healing and curatorship. How to perform the invisible? This conversation is about deep images, existential modes and bodily injuries of the earth and how our rituals, enchanted wisdoms, witchcraft and black, indigenous and trans macumbarias are dangers to the white and cisgender coloniality of art. What are the characteristics of art criticism from the Bantu cure? What are the ties of art curatorship that come undone from the transvestite anti-colonial cure? The ‘curanderia’ is the exercise of clinical redirection (surgical criticism of art) of some institutional artistic practices that need to be abandoned, also realizing those that must be reformulated.
Keywords: Healing processes; Curatorship; Art criticism; Anti-colonialities